Using a pressure mapping system to evaluate contact pressure on hands during use of axillary crutches - Silva, Danilo Corrêa [UNESP]; Medola, Fausto Orsi [UNESP]; Bonfim, Gabriel Henrique Cruz [UNESP]; Paschoarelli, Luis Carlos [UNESP] (IOS Press, 2015)
The aim of this study was to evaluate different handles used in axillary crutches with a Pressure Mapping System. The Grip Versatek system from Tekscan Inc. was used to measure the levels and the distribution of contact pressure in the hands during a simulated activity of ambulation with crutches. The sample included ten able-bodied subjects: five men and five women. The results show that the different models of handles appear to have influenced the pressure levels measured during the activity. Therefore, the measurement equipment provides parameters that allow the comparison among different designs and assess their contribution to the comprehension of the demands of ergonomic handles.